Moral hazard in VC finance: More expensive than you thought - Julius Tennert; Marie Lambert; Hans-Peter Burghof (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
Venture projects are fraught with exogenous market risk and endogenous agency risk. We apply a real options perspective to analyze the investment decision of the venture capitalist (VC) in this set-up. The solutions presented are conflictive: the VC reduces his exposure to exogenous risk by delaying investments to wait for informational updates (delay option), but he mitigates endogenous risk by advancing investments to discover entrepreneur's effort. So far, papers focus on the optimal timing of investments considering independence of exogenous and endogenous risk. We show that interdependence of exogenous risk and endogenous risk exists. We find that endogenous risk prompts the VC to accelerate the discovery process when exogenous risk is high, and to abandon the delay option when it is most valuable.
urn:nbn:de:bsz:100-opus-13315
Keywords: G11; G12; G24; D53; 330; Venture Capital; Real Option; Agency Cost; Moral Hazard